Toxicity of gold nanorods on zebrafish (Danio rerio) embryos - Mesquita, B.S. (2017)
Introduction: Gold nanoparticles (NPs) are being incorporated into various consumer products and are very promising in biomedicine as diagnostic and therapeutic delivery platforms. However, concerns about their safety, environmental and health impact have risen, as they might establish harmful interactions with biological systems. In this context, it is of major importance to understand the implications of exposure to these NPs on early life stages of biota, which have been considered, in general, as the most sensitive to chemical contamination. Objective: The present study aimed to evaluate the lethal and sublethal effects that gold nanorods (GNRs) may provoke on earlylife stages of the fish species Danio rerio.